Keberhasilan Corporate Turnaround Pada Perusahaan Yang Mengalami Financial Distress di Masa Pandemi COVID-19 - Ryan Chetta; Khomsiyah Khomsiyah (Owner : Riset dan Jurnal Akuntansi, 2022)
This study intended to examine how company turnover was measured in Indonesian stock real estate markets and real estate companies in 2019-2020. The logistic regression analysis of assets retrenchment, expense retrenchment, free assets, and company size was adopted for the study to quantify corporate turnaround. There were 76 firms involved in real estate and property, according to the Indonesia Stock Exchange. Only 56 real estate and property companies out of that total satisfy the requirements or were eligible to be included as the sample. The researcher employed the sampling approach to select a sample that met a set of criteria to determine this sample. The sample taken by the researcher is in the form of financial statements which are a source of quantitative data from the official website. The result of this study proves that free assets and company size have a positive and significant effect on a company’s ability to successfully implement a corporate turnaround as evidenced by a significance value of more than 0.05. Meanwhile, the variables of asset retrenchment and expenses retrenchment have no significant effect on the Company's success in carrying out corporate turnaround as evidenced by a significance value of less than 0.05.